Estimation of car braking parameters - Marijus Radavičius; Saulius Nagurnas (Lietuvos Matematikos Rinkinys)
In the paper the problem of prediction of car braking distance from its initial speed is considered. Based on the data of braking experiments, a regression model is fitted and validated and the covariance structure of the prediction errors is established.